Essentials of early English : an introduction to Old, Middle, and Early modern English - Smith, J. J. (Jeremy J.) (Routledge, 2005)
'Essentials of Early English' is a practical and highly accessible introduction to the early stages of the English language: Old English, Middle English, and Early Modern English. A bibliography is included and a glossary of key terms.